Axillary Web Syndrome Beyond Breast Cancer: Expanding the Clinical Spectrum Through Illustrative Cases and Contemporary Evidence - Nathalia Cardoso Oliveira; José Marcelo Corassa; Fanilda Souto Barros; Brenno Augusto Seabra de Mello Netto; Anke Bergmann; Joana Storino (Journal of Clinical Medicine, 2026)
Background/Objectives: This study aimed to expand the recognized clinical spectrum of Axillary Web Syndrome (AWS) by integrating illustrative oncologic and non-oncologic cases with a contemporary review of the evidence regarding its epidemiology, diagnosis, pathophysiology, and management. Methods: This study combines a retrospective case series of three patients diagnosed with AWS with a contemporary narrative review of the literature. The series included one patient following breast cancer surgery and two patients without oncologic history who developed AWS after repetitive upper-limb activity. Clinical presentation, ultrasonographic findings, treatment, and outcomes were analyzed. The literature review contextualized current evidence on the epidemiology, pathophysiological mechanisms, diagnostic approach, imaging assessment, differential diagnosis, and therapeutic management of AWS. Results: Three patients with AWS were identified, including one classic postoperative breast cancer case and two non-oncologic presentations following repetitive upper-limb activity. All patients presented with palpable subcutaneous cords, pain, and restricted shoulder abduction. Ultrasonography demonstrated no evidence of superficial thrombophlebitis or other structural abnormalities, supporting the exclusion of alternative diagnoses rather than confirming AWS. Conservative treatment consisting of physiotherapy, stretching exercises, and progressive shoulder mobilization resulted in symptom resolution and functional recovery in all cases. The literature review demonstrated that AWS may occur in a broader range of oncologic and non-oncologic settings than traditionally recognized, supporting the hypothesis that localized lymphovascular injury may contribute to a shared pathophysiological pathway across different clinical settings. Conclusions: AWS should be considered in the differential diagnosis of patients presenting with painful axillary cords and shoulder dysfunction, regardless of a history of breast cancer. Early clinical recognition, appropriate use of ultrasonography to exclude competing diagnoses, and timely conservative rehabilitation are essential to optimize functional recovery. These findings support a broader conceptual framework in which AWS may represent a clinical syndrome of localized lymphovascular injury rather than a complication restricted exclusively to breast cancer surgery.